Dealing with emotions of stakeholders during crises: Why should leaders care? - PANG, A. (Institutional Knowledge at Singapore Management University, 2013)
If crises are analogous to the howling winds during a nasty thunderstorm that wreak tumultuous havoc on the yacht that is the organization, then the emotions of stakeholders may be regarded as the sail that steers the yacht, sometimes towards uncharted waters, to the exasperation and befuddlement of the captain who is the CEO. Mainstream crisis research has for decades focused on examining organizational response based on strategies in times of crisis. The two dominant theories on crisis strategies, the image repair theory (see Benoitand Pang, 2008) and situational crisis communication theory (see Coombs, 2012) have been designed to understand what strategies are relevant to use under what circumstances. Image repair theory has been described as the “dominant paradigm for examining corporate communication in times of crises” (Dardis and Haigh, 2009, p. 101). As an extension of apologia (Coombs, Frandsen, Holladay, and Johansen, 2010), the theory asserts that an organization’s credibility largely depends on its image. When image is threatened, face works is used to repair image, argued Benoit and Pang (2008). This usually occurs when the accused is believed to have committed an offensive act by its salient audience (Benoit and Pang, 2008). Face, image, and reputation are extremely important commodities, argued Benoit and Pang (2008), because, as a society, we pride ourselves on, and value those who enact, tolerance and sensitivity to the feelings and tradition of others.